SHM_120941_HST_3D Ceramic Jug - Bonnevier, Helena; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a ceramic jug from the Middle Ages, collected in the field from Slottsfjärden in Kalmar and currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=655

Link to Sök I Samlingarna

https://samlingar.shm.se/object/24D0542B-6AE2-4270-9FFA-BFFD26856C57
Keywords: Museum Object; 3D Model; Archaeology; Archaeology; Photogrammetry; Archaeology/history; History and archaeology; Dynamic Collections; Slottsfjärden; Swedish Middle Ages; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi